Advances in Tourism, Technology and Systems Selected Papers from ICOTTS 2021, Volume 2 - Carvalho, João Vidal de; Liberato, Pedro; Peña, Alejandro (Smart Innovation, Systems and Technologies, 2022)
XIII, 617 p. 84 illus., 57 illus. in color.